Is SiPOERT an Innovative Learning? Implementation and Identification of Students’ Conception on Simple Harmonic Motion - Nurhasanah Nurhasanah; Achmad Samsudin; Suharto Linuwih; Asep Dedy Sutrisno (Universitas Muhammadiyah Surakarta, 2023)
The purpose of this research is to identify students’ conception of simple harmonic motion by implemen-ting SiPOERT (Simulation in Predict Observe Explain with Refutational Text). The research method used is mixed methods with an embedded mixed methods research design. The research instrument used consis-ted of diagnostic test questions in the format of four-tier Simple Harmonic Motion, Refutational Texts Student Worksheets, and learning implementation observation sheets. The sample in this study consisted of 32 students in XI class in one of the public high schools in Central Java. The analysis of this study uses delta M, the implementation of learning is shown in the form of a percentage, and the change in conception is analyzed based on the results of the pre-test and post-test. The results showed that students' misconcep-tions decreased by 16.4% from the pretest of 65.9% to 49.5% in the post-test. There was a change in the level of conception, by 42% in the Accepted Change (AC) category, 41% in the Not Change (NC) category, and 17% in the Unaccepted Change (UC) category.